Problems of Evil and the Power of God. By James A. Keller - Sturch, Richard (The journal of theological studies, 2009)
Of possible responses to the problem of evil, that which suggests a God limited in power (and perhaps in knowledge), which was popular in the first part of the twentieth century, seems to have fallen into disfavour. Professor Keller aims to revive it., He begins conventionally enough with the traditional problem of evil, moral and natural, and the main responses made by traditional theists (believing in a God who is omnipotent, omniscient, and all-good). Although he is plainly not happy with many of these responses, he concludes that traditional theism can hold its ground if it maintains that God has a general policy of allowing the universe to operate by law and human beings to have free will (though the former does not square well with a belief in miracles).